Programma: 9 juli Sera Me Monniken, Chris Hinze; 10 juli Alt, The Mutton Birds; 12 juli Tapesh; 13 juli Scorn; 14 juli Spelen voor de GRAP
Programma: 9 juli Sera Me Monniken, Chris Hinze; 10 juli Alt, The Mutton Birds; 12 juli Tapesh; 13 juli Scorn; 14 juli Spelen voor de GRAP.